Surgical treatment of Behcet's disease with severe aortic regurgitation - Tang, Chuanbin; Song, Yu; Huang, Xiaofan; Li, Yuanming; Tuerxun, Yisilamujiang; Hu, Xingjian; Li, Huadong; Wu, Long (Frontiers in Cardiovascular Medicine, 2023)
Behcet's disease (BD) is a multisystem inflammatory disease that is characterized by oral aphthosis, genital aphthosis, ocular lesions, and cutaneous lesions. Although BD rarely involves the cardiovascular system, its symptoms can be shown as aortic regurgitation (AR), which requires surgical intervention. Due to the special pathogenesis of BD, a low preoperative diagnosis rate and a high incidence of serious complications, such as perivalvular leakage, valve detachment, and pseudoaneurysm after prosthetic valve replacement, surgical treatment of BD with severe AR has an poor prognosis. In recent years, new surgical strategies have been developed to improve treatment efficacy for this disease. This article reviews and summarizes the evolution of surgical techniques for BD with AR and aims to provide a reference for optimizing surgical strategies, improving perioperative management, and assisting prognosis in patients suffering from BD with severe AR.